Implementation of Children's Architectural Design Principles in Child-Friendly School Buildings (Case Study: Fuji Kindergarten, Japan & Farming Kindergarten, Vietnam) - Jessica Victoryana; Indri Astrina Wirakusumah; Iwan Sudradjat (Publikasi Indonesia, 2024)
Currently, there is a lack of comprehensive guidelines for child-friendly architecture that serve as a cohesive framework for designing spaces for children. Yet, architecture for children should be given greater priority to ensure adequate educational facilities for the next generation. Creativity is paramount in the development of fine and gross motor skills in children. In the related case study of Fuji Kindergarten, technical requirements related to the physical and motor development of children have been well addressed through the implementation of exceptionally designed spaces. Thus, the aspects implemented by Fuji Kindergarten in its design can serve as exemplary design principles. The method employed revolves around Sarah Scott's theory of architecture for children, which will be mapped onto the design features used by Tezuka Architect as the designer of Fuji Kindergarten. This will be further compared with the Farming Kindergarten in Vietnam, which also receives recognition in the category of children's architecture. This paper aims to raise awareness of the importance of architecture for children, serving as a formulation of concerns that may eventually lead to solutions for the issues in designing architectural spaces for children. Additionally, it serves as a comprehensive insight into designing children's architecture, particularly kindergarten spaces, drawing from the best practices in children's architecture typologies.